Taxonomy of the Liolaemus alticolor–bibronii Group (Iguania: Liolaemidae), with Descriptions of Two New Species - Quinteros, Andres Sebastian (2012)
Liolaemus alticolor is redescribed herein, providing new character states that distinguish this taxon from all other members of the alticolor–bibronii group. Two new species of the alticolor–bibronii group are also described. One of the new species occurs in northern Argentina, in the Jujuy Province, whereas the other occurs in southern Argentina, in the Neuquén Province (northern Patagonia). Both of them exhibit characters that distinguish them from each other and from all other members of the alticolor–bibronii group. A key to the species of this group is provided.